2018
DOI: 10.3390/medicines5020026
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Total Phenolic and Flavonoid Contents, Antioxidant and Photoprotective Activities of Crude Methanolic Extract of Aerial Parts of Capnophyllum peregrinum (L.) Lange (Apiaceae) Growing in Algeria

Abstract: Background: Capnophyllum peregrinum (L.) Lange (Apiaceae) is the unique taxon of capnophyllum genus in Algerian flora. It has never been investigated in regards to its total phenolic and flavonoid contents and antioxidant and photoprotective activities. Methods: C. peregrinum aerial parts extracted with absolute methanol. The total flavonoid and phenolic contents of the extract were evaluated to determine their correlation with the antioxidant and photoprotective activities of the extract. Results: The methano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 36 publications
1
25
2
2
Order By: Relevance
“…Of those alternatives, the natural sources originated antioxidants have been found as the champion one. Plants are in the front line as well-known homes of various natural antioxidants; which currently have been gained serious attentions (Khatoon et al, 2013;Lefahal et al, 2018;Truong et al, 2019). These medicinal plant based natural antioxidants have played tremendous roles on fighting free radicals via the chemistry of providing an electron and/or hydrogen and making the restless oxidative species stable (Rebaya et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Of those alternatives, the natural sources originated antioxidants have been found as the champion one. Plants are in the front line as well-known homes of various natural antioxidants; which currently have been gained serious attentions (Khatoon et al, 2013;Lefahal et al, 2018;Truong et al, 2019). These medicinal plant based natural antioxidants have played tremendous roles on fighting free radicals via the chemistry of providing an electron and/or hydrogen and making the restless oxidative species stable (Rebaya et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous extract 1 µL/mL 8 (Rosa et al 2008) Green propolis and red propolis Ethanolic and glycolic extract in a gel 0.2 µL/mL 2.2-5.8 (Nascimento et al 2009) Pothomorphe umbellate root Crude ethanol-water extract 0.2 µg/mL 21 (Da Silva et al 2005) Sonchus oleraceus Aqueous extract 1 µL/mL 6 (Rosa et al 2008) Brassica oleracea Aqueous extract 1 µL/mL 5 (Rosa et al 2008) Porophyllum ruderale Aqueous extract 1 µL/mL 5 (Rosa et al 2008) Plectranthus barbatus Aqueous extract 1 µL/mL 2 (Rosa et al 2008) Cyperus rotundus Aqueous extract 1 µL/mL 1 (Rosa et al 2008) Rutin -0.1% 1.1 (Velasco et al 2008) Passiflora incarnata Dry extract 1.68% 1.2 (Velasco et al 2008) Plantago lanceolata Hydroglycolic extract 2.78% 1.1 (Velasco et al 2008) Dracocephalum moldavica Ethyl acetate extract 2 mg/mL 24.79 (Khazaeli & Mehrabani 2008) Viola tricolor Ethyl acetate extract 2 mg/mL 25.69 (Khazaeli & Mehrabani 2008) Moringa oleifera Aqueous extract 4.0% 2.01 (Baldisserotto et al 2018) Capnophyllum peregrinum Crude methanolic extract 2 mg/mL 35.21 (Lefahal et al 2018) demonstrated by several previous studies (Wagner 2011). The SPF value is dependent on the molecule(s) present in the extracts that exhibit photoprotection ability, the method of extraction, the concentration of the substances, and the solvent or system in which it is incorporated.…”
Section: Achillea Millefoliummentioning
confidence: 99%
“…Whereas the in vivo test is time consuming and includes various degrees of variability. The SPF numbers of extracts were calculated by applying Mansur mathematical equation in the UV-B region, which is considered to be the region of highest incidence during the day and people are exposed for a longer time [34]. Whereas plant literature shows that natural substances extracted from plants have potential sunscreen activity as it gets absorbed in the UV region due to the presence of antioxidants [35].…”
Section: Determination Of In Vitro Spf Of Extractsmentioning
confidence: 99%